Constraining a black hole companion for M87* through imaging by the Event Horizon Telescope. (10th July 2019) - Safarzadeh, Mohammadtaher; Loeb, Abraham; Reid, Mark
ABSTRACT: The Event Horizon Telescope, a global very long baseline interferometric array observing at a wavelength of 1.3 mm, detected the first image of the M87 supermassive black hole (SMBH). M87 is a giant elliptical galaxy at the centre of the Virgo cluster, which is expected to have formed through merging of cluster galaxies. Consequently M87* hosted mergers of black holes through dynamical friction and could have one or multiple binary companions with a low mass ratio at large separations. We show that a long-term monitoring of the M87 SMBH image over ∼1 yr with absolute positional accuracy of 1 ≈μ as could detect such binary companions and exclude a large parameter space in semimajor axis ( a 0 ) and mass ratio ( q ), which is currently not constrained. Moreover, the presence of the accretion disc around M87* excludes a binary companion with a 0 ≈ of the order of a milliparsec, as otherwise the accretion disc would have been tidally disrupted.